Ripple effect of trump’s tariff on the stock market spill over in six Asian countries - Chang, Ling; Goh, Dickson; Ho, Chun Loong; Liau, Jia Hui; Puah, Yen Rou (2020)
Trade war happened when a nation imposed tariffs or limits the quotas on imports and another foreign country react with similar forms of trade to protect its own benefit. Most countries would impose tariff as their useful tools to control the trade deficit. In 2018, United States started a trade war with China with the reason to reduce the 621 billion US trade deficit. In our study, we are going to examine the trade war happened between United States and China that could possibilities affect the Asia countries’ stock market return. Throughout the past studies, most researchers focus on the impact of both US and China trade war by looking at the economic factors such as GDP, inflation and unemployment rate. Thus, we aim to focus on the trade pattern that could probably affect the stock market return and also spillover effect towards country. The reason that we narrow from economic factors to stock market is because it can be easy capture the spillover effect and stock market are more sensitive on news. We are using different test such as Panel Least Square, Autoregressive Conditional Heteroscedasticity (ARCH), Generalized Autoregressive Conditional Heteroscedasticity (GARCH) and Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) models to determine the spillover effect of the trade war on six countries which is Taiwan, Malaysia, Singapore, Japan, South Korea and Hong Kong. The period that we investigate starting from 22 Jan 2018 to 1 June 2019 total of eight scenario situation that US impose tariff and China retaliate. In the overall result, we conclude that Taiwan and Hong Kong are the biggest winner in this trade war. Both of the country gets positive impact more than negative impact in stock market while at the same time, Japan, South Korea, Taiwan and Malaysia react more on unexpected negative news. While as an overview, US and China move on to negotiation in order to lower down the loss for both and other countries. In trade world, many countries are connected globally and it is important that both countries have to step forward to solve the trade conflict.